2002
DOI: 10.1081/cnv-120005901
|View full text |Cite
|
Sign up to set email alerts
|

Low Molecular Weight Heparin for Venous Thromboembolism Prophylaxis in Urologic Oncologic Surgery

Abstract: Low molecular weight heparins appear promising for DVT prophylaxis in high-risk urology patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…With the advent of low molecular weight heparins, they have become the most common chemoprophylactic agents for DVT prophylaxis. Many studies have demonstrated lesser complications and greater Operation Group-I (N) Group-II (C) Total Cholecystectomy 5 3 8 CBD exploration 4 4 8 Rectal Operation 3 3 6 Exploratory laparotomy 14 14 28 Adrenalectomy 1 2 3 Oesophagectomy 1 0 1 Ilio-Inguinal lymph node dissection 3 4 7 Nephrectomy 3 1 4 Total 34 31 Table 1 Types of operations performed efficiency of LMWHs in preventing DVT compared to unfractionated heparin [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of low molecular weight heparins, they have become the most common chemoprophylactic agents for DVT prophylaxis. Many studies have demonstrated lesser complications and greater Operation Group-I (N) Group-II (C) Total Cholecystectomy 5 3 8 CBD exploration 4 4 8 Rectal Operation 3 3 6 Exploratory laparotomy 14 14 28 Adrenalectomy 1 2 3 Oesophagectomy 1 0 1 Ilio-Inguinal lymph node dissection 3 4 7 Nephrectomy 3 1 4 Total 34 31 Table 1 Types of operations performed efficiency of LMWHs in preventing DVT compared to unfractionated heparin [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies have evaluated thromboprophylaxis in other surgical oncology settings, including thoracic (Cade et al , 1983; Azorin et al , 1997), urologic (Bigg & Catalona, 1992; Sawczuk et al , 2002) and orthopaedic surgery (Lin et al , 1998). Based on limited published data, it appears that prophylaxis with either UFH or LMWH is effective and relatively safe, but properly conducted studies are needed to address the issue in each surgical setting separately.…”
Section: Surgical Settingmentioning
confidence: 99%
“…Very few studies have evaluated thromboprophylaxis in other surgical oncology settings, including thoracic (Cade et al, 1983;Azorin et al, 1997), urologic (Bigg & Catalona, 1992;Sawczuk et al, 2002) and orthopaedic surgery (Lin et al, 1998).…”
Section: Surgical Settingmentioning
confidence: 99%
“…In the study conducted by Sawczuk on 38 patients qualified for elective urologic cancer surgery, dalteparin (2500 units s.c., prophylaxis began 1-2 hours before surgery) along with intermittent pneumatic compression was used. Within 3-7 days of thromboembolism prophylaxis, there was no symptomatic VTE episode diagnosed and at the same time, no excessive bleeding was observed [232]. Koch assessed the effectiveness of enoxaparin administered an hour before surgery at the dose of 30 mg (and next after 12 hours) in patients undergoing open prostatectomy and did not report symptomatic VTE events in the group receiving prophylaxis, whereas 3.3% in the controls, who used only compression means, presented with thromboembolic events [233].…”
Section: Venous Thromboembolism Prophylaxis In Cancer Patientsmentioning
confidence: 93%
“…anti-androgen treatment), and, as in other medical fields, clinically significant concomitant disease presence [14,[205][206][207][208]. The presence of cancer also increases the risk for symptomatic VTE occurrence after upper urinary tract surgeries up to 1-5% [14,179,12,183].…”
Section: Venous Thromboembolism Prophylaxis In Cancer Patientsmentioning
confidence: 99%